Learning From Failure: How Founders Transform Startup Setbacks into Success - Permatasari, Karin Sufi; Santi Isnaini; Farisa Alyani Desnithalia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study explores how startup founders can transform early failures into long-term success. The research aims to identify key strategies and practices employed by founders to address and overcome failures. A Systematic Literature Review (SLR) methodology is utilized to analyze existing studies on startup failures and the recovery efforts undertaken by founders. The findings indicate that successful founders leverage strong business networks, continuous innovation, and personal motivation to propel their companies forward. Additionally, the development of a competent and diverse team, along with effective communication with investors, significantly enhances the likelihood of success. The study concludes that although early failures are common among startups, such failures can become valuable experiences that contribute to future success when managed strategically.